Large-Scale Expansion of Suspension Cells in an Automated Hollow-Fiber Perfusion Bioreactor - Eric Bräuchle; Maria Knaub; Laura Weigand; Elisabeth Ehrend; Patricia Manns; Antje Kremer; Hugo Fabre; Halvard Bonig (Bioengineering, 2025)
Bioreactors enable scalable cell cultivation by providing controlled environments for temperature, oxygen, and nutrient regulation, maintaining viability and enhancing expansion efficiency. Automated systems improve reproducibility and minimize contamination risks, making them ideal for high-density cultures. While fed-batch bioreactors dominate biologics production, continuous systems like perfusion cultures offer superior resource efficiency and productivity. The Quantum hollow-fiber perfusion bioreactor supports cell expansion via semi-permeable capillary membranes and a closed modular design, allowing continuous media exchange while retaining key molecules. We developed a multiple-harvest protocol for suspension cells in the Quantum system, yielding 2.5 × 1010 MEL-745A cells within 29 days, with peak densities of 4 × 107 cells/mL—a 15-fold increase over static cultures. Viability averaged 91.3%, with biweekly harvests yielding 3.1 × 109 viable cells per harvest. Continuous media exchange required more basal media to maintain glucose and lactate levels but meaningfully less growth supplement than the 2D culture. Stable transgene expression suggested phenotypic stability. Automated processing reduced hands-on time by one-third, achieving target cell numbers 12 days earlier than 2D culture. Despite higher media use, total costs for the automated were lower compared to the manual process. Quantum enables high-density suspension cell expansion with cost advantages over conventional methods.